Implementation of Interactive Multimedia Edpuzzle in Economics Learning at MAN 1 Majene Regency - Ashari , Nurfathiha; Sahabuddin , Romansyah; Najamuddin , Najamuddin (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
This study aims to determine: 1) Describe the implementation process of Edpuzzle interactive multimedia in economics learning at MAN 1 Majene Regency. 2) Identify the obstacles faced by teachers in implementing Edpuzzle in economics learning at MAN 1 Majene Regency. 3) Analyze the effect of using Edpuzzle interactive multimedia on student engagement in economics learning at MAN 1 Majene Regency. The research method used is a descriptive quantitative approach method. The research variables consist of Edpuzzle Media (Variable X) and Economics Learning (Variable Y). Data collection techniques use observation, questionnaires and documentation. The data analysis techniques used are descriptive statistics and inferential analysis. Based on the results of the study that: 1) The use of Edpuzzle interactive multimedia in economics learning at MAN 1 Majene Regency has proven to be effective. Students feel the benefits in understanding the material, while teachers find it easier to compile interactive materials. Features such as interactive questions and progress tracking help student engagement. In addition, Edpuzzle's flexibility in distance learning and blended learning improves understanding and learning independence. 2). Constraints in implementing Edpuzzle include limited internet access, inadequate devices, and students' understanding of the platform. Teachers also have difficulty in adjusting appropriate materials and limited features of the free version. In addition, the lack of direct interaction makes some students tend to be passive or less focused on completing assignments. 3) The influence of Edpuzzle as a learning medium on economic learning is in the moderate category with a correlation of 0.397. The significance test shows that R count (0.397) > R table (0.284) and the Sig. value. (2-tailed) = 0.005 <0.05, so that the relationship between the two is positive and significant. This means that the higher the use of Edpuzzle, the better the students' understanding of economic subjects at MAN 1 Majene Regency